Sinergitas Aliran Positivisme dalam Filsafat Auguste Comte untuk Kemajuan Masyarakat Indonesia - Muhammad Luthfi Jalaludin Al-Habibi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the synergy of positivism in Auguste Comte's philosophy for the advancement of Indonesian society. This study uses a qualitative approach by applying descriptive methods. Auguste Comte's theory of positivism is positioned as a formal object, while the material object is the progress of Indonesian society. The results and discussion in this study show that Auguste Comte, through his thoughts on the progress of society, is contained in his positivism flow in the synergy of three stages, namely the theological, metaphysical, and peak stages of positivism, this is relevant as a reference for Indonesian society, especially by implementing the positivism stage. , so that society does not stagnate at the theological and metaphysical stages alone. This study concludes that Auguste Comte's philosophical positivism school is relevant for developing Indonesian people's thinking so that synergy does not stop at the theological and metaphysical stages, as a reference for the progress of Indonesian society.